ANALISIS PENGEMBANGAN KOMPONEN WISATA PANTAI PASIR PUTIH PARPAREAN DESA PARPAREAN II KECAMATAN PORSEA KABUPATEN TOBA - Lailan Rafina Marpaung; Eni Yuniastuti (Jurnal Samudra Geografi, 2026)
This study aims to identify the tourism components and analyze the development strategies of Parparean White Sand Beach. The research was conducted in Parparean II Village, Porsea District, Toba Regency. Data were collected through observation and interviews and analyzed using a qualitative descriptive approach. The results show that the tourism attraction component scored 4, categorized as moderate, while the amenity and accessibility components scored 19 and 8, respectively, both categorized as good. Tourism development strategies include improving existing tourism components, establishing cooperation with investors, conducting community outreach and forming a tourism management organization, enhancing order, comfort, cleanliness, and safety, and utilizing social media for tourism promotion.